Carotid Artery Stenting With Proximal Embolic Protection via a Transradial or Transbrachial Approach: Pushing the Boundaries of the Technique While Maintaining Safety and Efficacy. (August 2016) - Montorsi, Piero; Galli, Stefano; Ravagnani, Paolo M.; Tresoldi, Simone; Teruzzi, Giovanni; Caputi, Luigi; Trabattoni, Daniela; Fabbiocchi, Franco; Calligaris, Giuseppe; Grancini, Luca; Lualdi, Alessandro; de Martini, Stefano; et al.
Purpose: To compare the feasibility and safety of proximal cerebral protection to a distal filter during carotid artery stenting (CAS) via a transbrachial (TB) or transradial (TR) approach.Methods: Among 856 patients who underwent CAS between January 2007 and July 2015, 214 (25%) patients (mean age 72±8 years; 154 men) had the procedure via a TR (n=154) or TB (n=60) approach with either Mo.MA proximal protection (n=61) or distal filter protection (n=153). The Mo.MA group (mean age 73±7 years; 54 men) had significantly more men and more severe stenosis than the filter group (mean age 71±8 years; 100 men). Stent type and CAS technique were left to operator discretion. Heparin and a dedicated closure device or bivalirudin and manual compression were used in TR and TB accesses, respectively. Technical and procedure success, crossover to femoral artery, 30-day major adverse cardiovascular/cerebrovascular events (MACCE; death, all strokes, and myocardial infarction), vascular complications, and radiation exposure were compared between groups.Results: Crossover to a femoral approach was required in 1/61 (1.6%) Mo.MA patient vs 11/153 (7.1%) filter patients mainly due to technical difficulty in engaging the target vessel. Five Mo.MA patients developed acute intolerance to proximal occlusion; 4 were successfully shifted to filter protection. A TR patient was shifted to filter because the Mo.MA system was too short. CAS was technically successful in the remaining 55 (90%) Mo.MA patients and 142 (93%) filter patients. The MACCE rate was 0% in the Mo.MA patients and 2.8% in the filter group (p=0.18). Radiation exposure was similar between groups. Major vascular complications occurred in 1/61 (1.6%) and in 3/153 (1.96%) patients in the Mo.MA and filter groups (p=0.18), respectively, and were confined to the TB approach in the early part of the learning curve. Chronic radial artery occlusion was detected by Doppler ultrasound in 2/30 (6.6%) Mo.MA patients and in 4/124 (3.2%) filter patients by clinical assessment (p=0.25) at 8.1±7.5-month follow-up.Conclusion: CAS with proximal protection via a TR or TB approach is a feasible, safe, and effective technique with a low rate of vascular complications.